Respuesta :

Let’s say that the present age of Marina’s daughter is ‘x’ years. Then 4 years ago, her age was (x - 4) years. Therefore, Marina’s age 4 years ago was: (x - 4) + 3(x - 4) = 4(x - 4) years. 6 years from now, the daughter’s age will be (x + 6) years, and Marina’s age will be: 2(x + 6) years.Now, 6 years from now will be (6+4), i.e., 10 years away from 4 years ago. Thus, Marina’s age 6 years from now can also be written as 4(x - 4) + 10 = (4x - 6) years. Therefore, 2(x + 6) = 4x - 6. Or, 2x + 12 = 4x - 6.


Or, 2x = 18.


Thus, the daughter’s age (x) = 9 years, and Marina’s present age = 4(x - 4) + 4 = 24 years.